Metabolic reprogramming in Helicobacter pylori infection: from mechanisms to therapeutics - Liu, Tong; Zhao, Xuelin; Cai, Ting; Li, Wei; Zhang, Minglin (Frontiers in Cellular and Infection Microbiology, 2025)
Helicobacter pylori (H. pylori), a key gastric mucosal pathogen, causes chronic gastritis, peptic ulcers, and gastric cancer. H. pylori remodel the gastric microenvironment through metabolic reprogramming to drive pathogenesis. CagA+ strains disrupt lipid metabolism, increasing non-alcoholic fatty liver disease, cardiovascular, and Alzheimer’s risks via PPAR interference, GBA1 demethylation, and altered FABP1/APOA1 expression, reversible by eradication. In glucose metabolism, H. pylori promote carcinogenesis via Lonp1-induced glycolysis, PDK1/Akt dysregulation, and HKDC1/TGF-β1/MDFI-mediated epithelial-mesenchymal transition, while exacerbating high-fat diet-induced dysbiosis. Infection manipulates macrophage immunometabolism. Bacterial utilization of host L-lactate through H. pylori gene clusters enables proliferation, gland colonization, and immune evasion by suppressing complement activation and TNF/IL-6 secretion. Lactate-targeting strategies show therapeutic promise. Amino acid dysregulation involves H. pylori biotin protein ligase (HpBPL)-mediated catabolism and γ-glutamyl transpeptidase-induced glutathione hydrolysis, depleting antioxidants while inducing dendritic cell tolerance. branched-chain amino acids accumulation activates mTORC1, and cystine-glutamate transporter inhibition with miR-30b upregulation exacerbates mucosal damage, forming a self-sustaining “metabolic reprogramming-immune evasion-tissue destruction” cycle. These mechanisms collectively enable H. pylori to propel gastric carcinogenesis, highlighting metabolism-targeted interventions as future solutions. This review summarizes how H. pylori remodel the gastric microenvironment and drives pathogenesis by manipulating host lipid, glucose, lactate, and amino acid metabolism.